Implementation of a Stand-alone Hybrid Distribution Generation System for Rural Power Distribution Network - Shaari S.A.; Hock G.C.; Hamid S.H.A.; Phing C.C.; Kiong T.S.; Hasya N.A. (Institute of Electrical and Electronics Engineers Inc., 2023)
Diesel engines; Engineering research; Environmental impact; Geographical distribution; MATLAB; Diesel powered generator; Distribution generation; Distribution systems; Electrification systems; Optimal placements; Radial distribution networks; Rural distribution networks; Rural power distribution networks; Rural areas